Pulmonary Surfactant and Drug Delivery: An Interface-Assisted Carrier to Deliver Surfactant Protein SP-D Into the Airways - García-Mouton, Cristina; Hidalgo, Alberto; Arroyo, Raquel; Echaide, Mercedes; Cruz, Antonio; Pérez-Gil, Jesús (Frontiers in Bioengineering and Biotechnology, 2021)
This work is focused on the potential use of pulmonary surfactant to deliver full-length recombinant human surfactant protein SP-D (rhSP-D) using the respiratory air-liquid interface as a shuttle. Surfactant protein D (SP-D) is a collectin protein present in the pulmonary surfactant (PS) system, involved in innate immune defense and surfactant homeostasis. It has been recently suggested as a potential therapeutic to alleviate inflammatory responses and lung diseases in preterm infants suffering from respiratory distress syndrome (RDS) or bronchopulmonary dysplasia (BPD). However, none of the current clinical surfactants used for surfactant replacement therapy (SRT) to treat RDS contain SP-D. The interaction of SP-D with surfactant components, the potential of PS as a respiratory drug delivery system and the possibility to produce recombinant versions of human SP-D, brings the possibility of delivering clinical surfactants supplemented with SP-D. Here, we used an in vitro setup that somehow emulates the respiratory air-liquid interface to explore this novel approach. It consists in two different compartments connected with a hydrated paper bridge forming a continuous interface. We firstly analyzed the adsorption and spreading of rhSP-D alone from one compartment to another over the air-liquid interface, observing low interfacial activity. Then, we studied the interfacial spreading of the protein co-administered with PS, both at different time periods or as a mixed formulation, and which oligomeric forms of rhSP-D better travelled associated with PS. The results presented here demonstrated that PS may transport rhSP-D long distances over air-liquid interfaces, either as a mixed formulation or separately in a close window time, opening the doors to empower the current clinical surfactants and SRT.